Pengaruh Budaya Kerja, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Office PT. Antareja Mahada Makmur Kutai Kartanegara - Anggita Ratna (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine the influence of work culture on the performance of office employees of PT. Antareja Mahada Makmur, the influence of the work environment on the performance of office employees of PT. Antareja Mahada Makmur, the influence of work discipline on the performance of office employees of PT. Antareja Mahada Makmur and the influence of work culture, work environment and work discipline on the performance of employees of PT. Antareja Mahada Makmur simultaneously. The subjects of the study were 45 employees of PT. Antareja Mahada Makmur. The sampling technique used simple random sampling. The measurement scale used in this study was the Likert scale. The data analysis technique used in the study was multiple linear analysis. The results showed that the F count value of 115.795> F table 2.83 and a significance level of 0.000 <0.05, meaning that the hypothesis was accepted, where there was an influence between the variables of work culture, work environment and work discipline simultaneously on the performance of employees of PT. Antareja Mahada Makmur. Then each variable of work culture, work environment and work discipline affects the performance of employees of PT. Antareja Mahada Makmur with a significance value of 0.000 < 0.05.